2013 Updated American Society of Clinical Oncology/Oncology Nursing Society Chemotherapy Administration Safety Standards Including Standards for the Safe Administration and Management of Oral Chemotherapy - Neuss, Michael N. (American Society of Clinical Oncology, 2013)
In 2009, ASCO and the Oncology Nursing Society (ONS) published standards for the safe use of parenteral chemotherapy in the outpatient setting, including issues of practitioner orders, preparation, and administration of medication. In 2011, these were updated to include inpatient facilities. In December 2011, a multistakeholder workgroup met to address the issues associated with orally administered antineoplastics, under the leadership of ASCO and ONS. The workgroup participants developed recommended standards, which were presented for public comment. Public comments informed final edits, and the final standards were reviewed and approved by the ASCO and ONS Boards of Directors. Significant newly identified recommendations include those associated with drug prescription and the necessity of ascertaining that prescriptions are filled. In addition, the importance of patient and family education regarding administration schedules, exception procedures, disposal of unused oral medication, and aspects of continuity of care across settings were identified. This article presents the newly developed standards.